2017
DOI: 10.1111/1750-3841.13662
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drink Induced Lipid Peroxidation and Oxidative Damage in Rat Liver and Brain When Used Alone or Combined with Alcohol

Abstract: Energy drinks (ED) are containing large doses of metabolic stimulants and its use with ethanol has increased dramatically among young adults. In this study, we examined the effects of ED exposure either alone or in combination with ethanol on oxidative stress parameters including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and lipid peroxidation parameter malondialdehyde (MDA) in rat. Some histopathological findings were also evaluated. ED exposure led to a dose-dependent incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 28 publications
3
25
0
2
Order By: Relevance
“…These results were in agreement with Reis et al [27] and Mansy et al [28] . Seifert et al [2] found that these effects may be caused by the mixture of various ingredients in the ED due to synergistic interaction and augmented oxidative effect of them.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were in agreement with Reis et al [27] and Mansy et al [28] . Seifert et al [2] found that these effects may be caused by the mixture of various ingredients in the ED due to synergistic interaction and augmented oxidative effect of them.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were due to different reaction of taurine with caffeine present in the energy drink. While Ebuehi et al [37] and Reis et al [27] found no changes in brain tissue although presence of biochemical alterations. They explained this by the short time of exposure to produce brain damage.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, the levels of MDA increased significantly in tissue samples of rats treated with APAP. These findings are similar to the results of other studies where increased tissue MDA levels were reported [31,32] after the application of some toxic substances in mice and rats.…”
Section: Discussionsupporting
confidence: 92%
“…The intense lipid peroxidation in biological membranes leads to the loss of fluidity, a decrease in the membrane potential, the increased permeability for H + and other ions and, in the end, a membrane rupture may also occur with the release of cellular content into extracellular space 47 . Our results are consistent with an increase in lipid peroxidation observed in the liver and brain of rats, after 14 days of using another commercially available ED 48 . In the chED-T group, an increased level of prooxidative species, О 2 and H 2 O 2 , was also registered, when compared to the C-T.…”
Section: Discussionsupporting
confidence: 91%